Conserved Antigenic Structure of Contemporary Wild Poliovirus Type 1 Strains Endemic in Pakistan . (17th November 2021) - Alam, Muhammad Masroor; Ikram, Aamir; Mahmood, Nayab; Sharif, Salmaan; Shaukat, Shahzad; Fatmi, Muhammad Qaiser; Angez, Mehar; Khurshid, Adnan; Rehman, Lubna; Akhtar, Ribqa; Mujtaba, Ghulam; Arshad, Yasir; et al.
Abstract: Background: Elimination of poliovirus in Pakistan and Afghanistan is challenged by notions against the role of oral poliovirus vaccine (OPV) in eradicating contemporary wild poliovirus (WPV) strains. Methods: A total of 1055 WPV type 1 (WPV1) strains isolated between 2013 and 2018 were categorized into 68 antigenic groups and tested for neutralization by OPV-derived antibodies. Molecular docking was conducted to determine neutralization efficiency of antibodies against WPV. The clinical significance of WPV1 variants was assessed to ascertain their role in patient outcomes. Results: We found that 88% of WPV1 strains isolated from paralytic children belonged to a single antigenic lineage identical to the WPV1 strain detected in 1993. WPV1 antigenic variants were effectively neutralized by OPV-derived antibodies, with geometric mean titers comparable to the neutralization titers found for 3 strains in OPV (OPV1–3, 7.96–9.149 [95% confidence interval, 6.864–10.171]; WPV1 strains, 7.542–8.786 [6.493–9.869]). Docking examination underscored a strong antigen-antibody interaction despite variations within the viral protein 1 epitopes. There was no significant association ( P = .78) with clinical prognosis among patients infected with antigenically diverse WPV1 strains and patient outcomes, including death. Conclusions: Our findings substantiate the robustness of OPV for neutralizing the contemporary WPV1 strains endemic in Pakistan and Afghanistan. Vaccination coverage must be augmented to achieve early eradication. Abstract : Wild poliovirus type 1 (WPV1) detected in Pakistan and Afghanistan showed strict antigenic stability across the viral protein 1 gene. Contemporary WPV1 strains were completely neutralized by oral poliovirus vaccine–derived antibodies, used across both countries to achieve poliomyelitis eradication.